2008
DOI: 10.1007/s00702-008-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological characteristics as predictors of SSRI treatment response in depressed subjects

Abstract: Studies suggest that neuropsychological measures may provide prognostic information regarding SSRI treatment response, yet it is unclear which specific cognitive domains are the most effectual predictors. The aim of this study was to characterize the cognitive profile associated with SSRI nonresponse using a comprehensive set of neuropsychological tests. Participants (N = 32) met criteria for current major depressive episode. Assessment followed pre-treatment medication washout. Clinical response was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 28 publications
4
67
1
Order By: Relevance
“…Within this work, there are also suggestions that performance on some of these tests may predict antidepressant medication outcomes (Supplementary Table 1) that formed in part the basis for the International Study to Predict Optimized Treatment in Depression (iSPOT-D) (Williams et al, 2011). Specifically, prior smaller-scale studies suggest that poor cognitive performance, such as working memory on the N-back task (Gorlyn et al, 2008), information processing speed on the digit symbol task (Leuchter et al, 2004), executive functioning and flexibility on the Wisconsin Card sort task (Dunkin et al, 2000), and color naming on the color and word Stroop task (which may reflect psychomotor slowing) (Taylor et al, 2006), all predicted worse outcome with an acute course of antidepressant treatment (Supplementary Table 1). Importantly, these findings regarding treatment outcome suggest that there may be a relationship between the pathophysiology of depression, which includes a broadbased dysfunction in cognition, and the capacity of these individuals to respond to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this work, there are also suggestions that performance on some of these tests may predict antidepressant medication outcomes (Supplementary Table 1) that formed in part the basis for the International Study to Predict Optimized Treatment in Depression (iSPOT-D) (Williams et al, 2011). Specifically, prior smaller-scale studies suggest that poor cognitive performance, such as working memory on the N-back task (Gorlyn et al, 2008), information processing speed on the digit symbol task (Leuchter et al, 2004), executive functioning and flexibility on the Wisconsin Card sort task (Dunkin et al, 2000), and color naming on the color and word Stroop task (which may reflect psychomotor slowing) (Taylor et al, 2006), all predicted worse outcome with an acute course of antidepressant treatment (Supplementary Table 1). Importantly, these findings regarding treatment outcome suggest that there may be a relationship between the pathophysiology of depression, which includes a broadbased dysfunction in cognition, and the capacity of these individuals to respond to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…First, we examined the formulation of depression as a disorder in which cognitive and emotional capacities are perturbed by determining whether performance in the behavioral battery would differentiate depressed participants from matched healthy controls, and whether heterogeneity in behavioral performance within the depression group contributed to the differentiation from controls. Second, we assessed whether behavioral performance could predict treatment outcome to each of the three antidepressant medications, predicting based on prior work ( (Gorlyn et al, 2008;Leuchter et al, 2004;Dunkin et al, 2000;Taylor et al, 2006) and Supplementary Table 1) that nonresponders would be characterized by impaired cognitive functioning relative to responders. Third, we tested whether the prediction generated for one antidepressant medication supported the ability to select between medications in the study, by virtue of differentially predicting outcome to this medication vs the others.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypotheses were that (1) following Majer et al [8] , Etkin et al [24] , Gorlyn et al [25] , and Taylor et al [32] , a higher performance in attention (alertness, divided attention, and working memory) would predict a more positive treatment outcome, (2) following Oral et al [9] , low baseline sBDNF levels would correlate with poor cognitive functions, and (3) improvement in cognitive functions would be associated with higher levels of sBDNF.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, studies on late-life depression have shown an impairment of executive functions to be associated with nonresponse to a selective serotonin reuptake inhibitor (SSRI) [25,[27][28][29][30][31] . Moreover, psychomotor slowing [32] and deficits in working memory [25] have also been indicative of poor treatment outcome. Concerning the cognitive function of attention, Majer et al [8] found that a greater impairment in divided attention at baseline predicted delayed response to antidepressant treatment and a higher risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation